Shared Spaces or Shelters for Precarious Workers? Coworking Spaces in Italy - Pacchi, Carolina; Mariotti, Ilaria (Professions and Professionalism, 2021)
This paper critically discusses the relationship between new workspaces, such as Coworking Spaces (CSs), professionals using such spaces, and the related work patterns, looking at the Italian context in particular. There appears to be a mismatch between the educational level of such workers, their expertise and expected professional status on the one hand, and their reality in terms of employment precariousness and low income, on the other. It appears that CSs and, more in general, new shared workspaces act more as shelters from a difficult and exclusionary job market than as mainly ‘serendipity accelerators’. The hypothesis of this article is that, through a careful interpretation of the emerging dimensions and spatial effects of CSs, it is possible to more clearly identify some dynamics of inclusion and exclusion on the one hand, and of sharing and competition on the other, that characterize the job path of new knowledge-based occupational groups.